Synergistic effects of vedolizumab and JAK 1,2,3 inhibitors in Crohn’s disease: insights from a systems biology and artificial intelligence-based approach - Marín-Jiménez, Ignacio; Sierra-Ausín, Mónica; Letosa-Abián, Teresa; Aparicio, Jesús; Montoto-Otero, Carmen; Sánchez-Ramón, Silvia (Frontiers in Immunology, 2025)
Background and aimsWhile current therapies for Crohn’s disease (CD), including vedolizumab (VDZ) and Janus kinase inhibitors (JAKi), have shown efficacy individually through different mechanisms of action, their combination may offer a more integrated approach, potentially improving outcomes for refractory or severe CD patients. By leveraging in silico systems biology and artificial intelligence, we provide a valuable method to understand the molecular mechanisms underlying this combined therapy.MethodsCD, VDZ, and JAKi were characterised at protein level by compiling data from extensive literature review and official documents. CD protein effectors were identified and used to construct mathematical models using Therapeutic Performance Mapping System (TPMS) technology. Sampling-based methods were employed to assess the impact of the combined VDZ plus JAKi therapy on CD and to unveil underlying molecular mechanisms.ResultsDisease characterisation identified 4 pathophysiological processes (referred to as motives, M) underlying the manifestation of the disease: intestinal barrier disruption (M1), altered innate immune response (M2), chronic inflammation and predominant Th1/Th17 adaptive immune response (M3), and tissue remodelling (M4). The combination of VDZ and JAKi modulated more effectors of CD (54.8%) than each drug did individually, thereby enhancing the effects of each drug. The combination therapy modulated 45 effectors (36%) through convergent mechanisms, primarily impacting M3, and also provided complementary mechanisms across all motives, but mainly in M1 and M4.ConclusionsOur results provide a mechanistic rationale for combining VDZ and JAKi as a potential therapy for CD, advancing the development of more effective and personalised treatment strategies.